Regulação de metaloproteinases da matriz pela força mecânica e ativação de receptores tipo Toll em fibroblastos do ligamento periodontal humano - Rodolfo Assis Lisboa (2012)
The use of mechanical force is the main planed event during the orthodontic treatment aiming to produce tooth movement. MMPs are known to play a key role during this treatment leading to periodontal tissue remodeling and, therefore, tooth movement. It is known that MMPs may be induced by mechanical forces, but it is not clear if the isolated activation of TLRs in periodontal fibroblasts may regulate the effects of the mechanical force. This force may be overestimated in the treatment of patients presenting periodontal bacterial infection what may lead to over absorption of the periodontal tissue and, consequently, treatment failure. To study this possibility, we submitted primary cultures of human periodontal fibroblasts to centrifugation in the presence of LPS and Pam-3-cys, known TLR 2 and 4 respective ligands. The expression of MMP-1, -2, -3, -8, -9, -10, -13, TIMP-1, -2, -4, TNF-, IL-1, ERK 1/2, p38, JNK, IRAK 1, NF-B and the activity of MMP-2 were measured by antibody array, ELISA, western blotting and gel zymography. We observed no increase in cell death associated to the simultaneous stimuli used in this study. As expected, the activity of MMP 2 was increased in cell cultures treated by a combination of LPS and Pam-3-cys. Interestingly, this combination reversed the inhibitory effect of centrifugation in the activity of MMP2. The activation of TLRs associated to centrifugation also induced na increase in the expression of MMP-1, -3, -10, phospho p38, phospho JNK and phospho NF-B without an increase in TIMPs. These findings suggest that MMPs may also be regulated by TLRs activation during the application mechanical forces in isolated cultures of periodontal ibroblasts via p38, JNK and NF-B pathways.